In situ observation of melting behavior of ZnTe nanowires - Shaygan, Mehrdad; Gemming, Thomas; Bezugly, Viktor; Cuniberti, Gianaurelio (Giovanni); Lee, Jeong-Soo; Meyyappan, M. (Journal of Physical Chemistry C, 2014)
The melting behavior of ZnTe nanowires has been investigated using a transmission electron microscope in both bright field and high-angle annular dark field modes. The ZnTe nanowires, 30-160 nm in diameter, were heated using a controllable heating system, and their melting temperature was studied. The results showed a significant reduction of the melting temperature of about 450 °C, depending on the diameter of the nanowire, compared to the bulk melting point of 1300 °C. In addition, scanning transmission electron microscopy using high-angle annular dark field imaging was carried out to structurally analyze the ZnTe nanowires after melting. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20